DEVELOPMENT OF MATHEMATICAL MODULES OF ALGEBRA MATERIAL BASED ON LEARNING CYCLE MODEL FOR STUDENTS IN CLASS VII - Caraka Kresna; Suparman Suparman (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
Mathematics learning media can help students understand abstract mathematical concepts, but the availability of learning media in school is still limited. This research aims to develop mathematics learning media in the form of learning model module learning cycle on algebra material for Junior High School Students in Grade VII, which is decent to apply in the process of learning mathematics. This research includes research development that using research and development methods, which consists of ten stages: potential and problem, data collection, product design, design validation, design revision, product trial, product revision, trial usage, product revision, and mass production. The object of this research is learning media that is a mathematics module, and the subjects are material experts, media experts, and students of State Junior High School 13 Tanjung Jabung Timur (SMPN 13 Tanjung Jabung Timur) and State Junior High School 21 Tanjung Jabung Timur (SMPN 21 Tanjung Jabung Timur). The data collection techniques are interviews, questionnaires, and observations. The data analysis technique uses a Likert analysis. The learning media product developed has been assessed and validated by three learning material experts and 3 mathematics learning media experts. The learning material experts' assessment results obtained with an average value of 97.67 indicate the category is very decent. The assessment results of learning media experts obtained with an average value of 61.33 indicate the category is decent. The assessment results of student responses obtained with an average value of 134.6105 show a very decent category. Based on these results, it can be concluded that the learning media, which is developed, is decent to apply in the learning mathematics process.